NUTRITIONAL INTERVENTION WITH FLAXSEED FOR UTERINE HEALING AND FERTILITY ENHANCEMENT IN SUBCLINICAL ENDOMETRITIS AFFECTED CROSSBRED DAIRY COWS - V. Reshma; R. Suresh Kumar; T. Sathiamoorthy; T. Devi; K. Ravikumar (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Subclinical endometritis (SCE) is characterized by increased polymorphonuclear neutrophils (PMNs) in the endometrium without clinical signs of uterine infection. This condition adversely affects fertility and herd productivity. The present study aimed to assess the efficacy of dietary flaxseed supplementation in improving uterine health and reproductive performance in lactating dairy cows diagnosed with SCE. Twelve SCE- positive cows, confirmed by the White Side Test (WST) and endometrial cytology (>5% PMNs), were randomly assigned to two groups: Group I (control; n=6) received a standard ration, and Group II (treatment; n=6) supplemented with flaxseed concentrate for three months. Post-treatment evaluation after second subsequent estrus revealed a significant improvement of the uterine status in the flaxseed-supplemented group. WST positivity declined from 100% to 16.67% in Group II, as compared to 66.67% in the control group. PMN percentage significantly decreased from 15.74 ± 0.99% to 3.67 ±0.55% in the flaxseed group, whereas a lesser decline (13.67 ± 0.67% to 5.33 ± 0.39%) was observed in controls. Conception rate was markedly higher in the flaxseed group (83.33%) compared to the control group (33.33%). The results demonstrated that the flaxseed supplementation effectively reduced uterine inflammation and enhances fertility in SCE-affected cows, offering a practical nutritional strategy for dairy herd reproductive management.